Prospects of botanical biopesticides in insect pest management - Hanem Fathy Khater (Journal of Applied Pharmaceutical Science)
Please note that the article entitled 'Prospects of botanical biopesticides in insect pest management' by Hanem Fathy Khater (J App Pharm Sci. 2012; May 2 (5): 244-259.) has been retracted as author submitted it elsewhere for simultaneous consideration..